R=GmKF

Rewrite the equation as GmKF=R.

GmKF=R

To remove the radical on the left side of the equation, square both sides of the equation.

GmKF2=R2

Multiply the exponents in ((GmKF)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(GmKF)12⋅2=R2

Cancel the common factor of 2.

Cancel the common factor.

(GmKF)12⋅2=R2

Rewrite the expression.

(GmKF)1=R2

(GmKF)1=R2

(GmKF)1=R2

Simplify.

GmKF=R2

GmKF=R2

Multiply each term by F and simplify.

Multiply each term in GmKF=R2 by F.

GmKF⋅F=R2⋅F

Cancel the common factor of F.

Cancel the common factor.

GmKF⋅F=R2⋅F

Rewrite the expression.

GmK=R2⋅F

GmK=R2F

GmK=R2F

Rewrite the equation as R2F=GmK.

R2F=GmK

Divide each term by R2 and simplify.

Divide each term in R2F=GmK by R2.

R2FR2=GmKR2

Cancel the common factor of R2.

Cancel the common factor.

R2FR2=GmKR2

Divide F by 1.

F=GmKR2

F=GmKR2

F=GmKR2

F=GmKR2

Solve for F R = square root of (GmK)/F